IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DALAM MENDUKUNG PELAYANAN ADMINISTRASI DI SEKOLAH TINGGI ILMU MANAJEMEN (STIM) BANDA ACEH - Fahmiwati Fahmiwati; Fadli Syahputra; T. Khairol Razi; Mahrul Mazi (Jurnal Real Riset, 2021)
Based on the situation in the field, the author analyzes that problems are found in both the management of academic data, lecturers and education staff that are not reported, the information system of higher education databases whose academic activities have not been reported, and the educational administration process that has not been going well and perfectly. The Banda Aceh School of Management (STIM) realizes the importance of information system practices combined with advances in information technology developed in reliable information systems in improving the quality of education, so as to produce accurate, up to date information that can be enjoyed by all users of education services. and make excellence in providing educational services. The research objectives were to determine the implementation of the Management Information System, to know the collection, management and storage of data through the management information system, and to find out the Administrative Services at STIM Banda Aceh.This type of research uses qualitative research methods, and the source of the data is the person (resource) is a data source that usually provides data in the form of oral answers through interviews from the Banda Aceh School of Management (STIM). The study was conducted from 01 to 17 August 2020 at STIM Banda Aceh, and data analysis using descriptive analysis techniques was carried out through three activity lines, namely: Data Reduction, Data Presentation, and Verification or Conclusion.The results showed that in implementing management information systems to support administrative services at STIM Banda Aceh, staffing and administration are the most important parts of an institution that is in charge of coordinating all divisions and is directly responsible to top management/chairman which includes the data collection section, the input section, data, the data storage section, everything is done by the operator and coordinated by the head of PTS data management. So it can be said that in education or a college cannot achieve the desired goal without the contribution of academic administration staff, staffing, and administration.It is hoped that the leadership and staff of STIM Banda Aceh can improve services creatively and innovatively and implement them effectively and efficiently.Keywords: Management information System, Administrative Services